PERANCANGAN TK DAN PAUD ISLAM TERPADU BINTANG PRAMUKA DI BANJARMASIN - Khozizah Khozizah; Anna Oktaviana (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
At this time in Banjarmasin City the number of children is increasing. So that the need for education for children starting from an early age, at an early age children are easier to teach something because their curiosity at that time is quite great. Good early childhood education is not only seen from the teaching pattern, but also the building that becomes a container or place where learning takes place, an interesting and safe building will make children more excited in following the stages of education. The stages of children's education are given based on age development and children's skills that are different from each other. Metaphoral Architecture is one of the design methods that is felt to be in accordance with the thoughts of children who at an early age or kindergarten tend to be simpler in assessing something that is seen combined with the Deep Learning Joyful Learning approach which this approach refers to an interesting and fun education for children.